Evaluation of the Implementation of Electronic Parking on Oto Iskandar Dinata Street in Bandung City - Rahmat Kartiwa (Social Impact Journal, 2025)
Terminal Parking Electronic (TPE) is an electronic parking fee payment system designed by computer. Electronic Parking Terminals are usually located on the roadside or certain places. The use of TPE (Electronic Parking Terminal) is expected to improve services to the community, especially in terms of electronic-based parking services. Talking about the tariffs installed, of course this is based on regional regulations. The objectives of the research are 1) to evaluate the implementation of electronic parking on Oto Iskandar Dinata Street, Bandung City; 2) to find out the obstacles that occur so that the electronic parking terminal (TPE) policy is not maximized. The method used in the research is descriptive qualitative approach method In this case, the author wants to describe the evaluation of the implementation of electronic parking in Bandung City (case study of Jalan Oto Iskandar Dinata). With data collection techniques namely observation, interviews, and documentation. The results of this study are 1) the TPE program in Bandung City has been running in accordance with applicable regulations but has not been optimal in other evaluation indicators that have not been met. 2) the existence of inhibiting factors from the implementation of the automatic parking terminal program is public awareness in using TPE which is not in accordance with the objectives of the program that has been launched then inadequate parking facilities, parking payment systems that are not optimal and human resources as levy collectors whose numbers do not appeal to the existing workload